2016
DOI: 10.1161/strokeaha.116.013453
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Effect in Children With Stroke in the Nationwide Inpatient Sample

Abstract: Background and Purpose-Studies have demonstrated differences in clinical outcomes in adult patients with stroke admitted on weekdays versus weekends. The study's objective was to determine whether a weekend impacts clinical outcomes in children with ischemic stroke and hemorrhagic stroke. Methods-Children aged 1 to 18 years admitted to US hospitals from 2002 to 2011 with a primary discharge diagnosis of ischemic stroke or hemorrhagic stroke were identified by International Classification of Disease, 9th Revisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Studies of ischemic stroke in children report incidences ranging from 0.6-7.9/100,000 children per year. 2,3,16,[19][20][21][22][23][24][25][26] Our incidence is consistent with recent studies using similar populations and methods. 22,24 We found endovascular therapy codes in 1% of our AIS cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Studies of ischemic stroke in children report incidences ranging from 0.6-7.9/100,000 children per year. 2,3,16,[19][20][21][22][23][24][25][26] Our incidence is consistent with recent studies using similar populations and methods. 22,24 We found endovascular therapy codes in 1% of our AIS cohort.…”
Section: Discussionsupporting
confidence: 92%
“…While studies have shown a weekend effect for different medical conditions (including acute kidney injury [ 4 ], pneumonia [ 5 ] or dysrhythmia [ 6 ]) major commonalities among conditions affected by a weekend effect are the need for time sensitive interventions and care at an intensive care unit. In line with this, there are numerous reports about a weekend effect for stroke [ 7 9 ] myocardial infarction [ 10 , 11 ] or pulmonary embolism [ 12 , 13 ]. Additionally, a growing body evidence points towards a weekend effect for conditions requiring emergency surgery e.g.…”
Section: Introductionmentioning
confidence: 73%
“…Of those that showed a significant adverse weekend effect, one assessed 19 386 children aged 1–18 years of age in the USA who were admitted with ischaemic or haemorrhagic stroke 5. A limitation of the study was that it relied on the correct coding of the diagnoses in the database 5.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the study was that it relied on the correct coding of the diagnoses in the database 5. Another examined the outcome of 12 893 children older than or equal to 90 days admitted to a rural hospital in Kenya.…”
Section: Introductionmentioning
confidence: 99%